2013
DOI: 10.1007/978-3-642-53856-8_41
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Container Terminal Problems: An Integrated Solution Approach

Abstract: Abstract. Over the last decades, a great effort has been done in order to achieve a suitable management of international sea freight trade. The maritime container terminals are intermediate points aimed at exchanging containers within multimodal transport networks. The large number of decision problems brought together in these facilities and the way they are related to each other constitute a challenge for their managers. The goal of this work is to overview the most outstanding logistic processes in maritime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…departure time, is not always improving stacking algorithm itself (Van Asperen et al 2013). Here, more real context is claimed to be researched (Expósito-Izquierdo et al 2013). However, categorization of containers as basic information is seen a good influencing factor for e.g.…”
Section: Integrated Approaches For Interrelated Terminal Problemsmentioning
confidence: 99%
“…departure time, is not always improving stacking algorithm itself (Van Asperen et al 2013). Here, more real context is claimed to be researched (Expósito-Izquierdo et al 2013). However, categorization of containers as basic information is seen a good influencing factor for e.g.…”
Section: Integrated Approaches For Interrelated Terminal Problemsmentioning
confidence: 99%
“…In [55], some general guidelines for designing integration approaches for the main container terminal decision problems are provided. The authors concluded that "in-depth research of integration proposals within the seaside and yard area logistical problems is essential to increase and maintain a high productivity as well as produce real-context planning solutions.…”
Section: Integrationmentioning
confidence: 99%
“…Since the international sea freight trade has undergone a relevant growth over the last few decades (United Nations Conference on Trade And Development, http://www.unctad.org/), maritime container terminals have to better use and schedule their resources in order to efficiently face the operational and technical requirements of shipping companies. In this regard, as indicated by Nicoletti et al [1] and Expósito-Izquierdo et al [2], the time required to serve container vessels, since their arrival until their departure, is the most representative indicator used by the shipping companies when assessing the competitiveness of a given maritime container terminal. Moreover, the faster these tasks are made, the earlier the containers are available for withdrawal by the corresponding companies, and therefore there will be a better management of the whole terminal (Yeo [3]).…”
Section: Introductionmentioning
confidence: 99%